VALIDITY PRACTICAL GUIDE OF MATERIALS BIOTECHNOLOGY IN CLASS XII SMA/MA - Vivi Fitriani; Novita Sari (Jurnal Pelita Pendidikan, 2020)
Biotechnology is one of the most advanced sciences to make biotechnology the kind of science that students need to control. To give good mastery of biotechnology teachers must be able to do the right and appropriate learning in order to gain good understanding of students. One of the efforts to increase students understanding of biotechnology materials is to integrate learning materials with practical activities. This study is intended to provide a valid practical guide for grade XII SMA/MA biotechnology materials. It’s study for the practical guide development study on grade XII SMA/MA biotechnology materails done using the four-D models that consist of stage define, design, develop and dessimninate. Research is limited to the development stage of the validation. The define stage done analysis of the development of the lab guide consists of foreground, analysis of students, analysis of duty, analysis concepts and purpose analysis of learning. Desain stage conducted an exercise guide design corresponds to the students characteristic figure and the practical guide component. Stage develop conducted the practical guidance assessment by the validator. Research is done by dissemination of the stock of validity to 2 professors and 1 teachers. Research shows that the validity of the fight guide is 95% with very valid criteria. The practical guide to a highly developed for grade XII SMA/MA biotechnology material.